Character Education through Habituation of Religious Activities at SDIT Al-Khairiyah, Cilegon City - Safitri, Laila Nur; Jamaludin, Ujang; Ngulwiyah, Istinganatul (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Character education includes more than teaching morality and ethics. In addition, by instilling good habits, it is expected that students can feel or experience (affective), develop cognitive awareness about right and wrong and get used to doing it (psychomotor). Instilling character education can be carried out by an educational institution. Among the educational institutions that organize character building is the Integrated Islamic Elementary School (SDIT), which combines general education and religious values. It is because character education lies not only in the material being taught but also in the habituation of positive attitudes and actions, one of which is through the habituation of religious activities. This study thus aims to determine (1) the implementation of character education through the habituation of religious activities and (2) the character of class IV A students at SDIT Al-Khairiyah. The research method employed in this research was qualitative research, i.e., understanding phenomena in the form of natural objects by collecting data by triangulation. The data collection techniques utilized were interviews, and non-participatory observation, i.e., the researchers were not directly involved in the activities that took place at school but only as observers using field notes and documentation to support the research. The results of this study revealed that (1) schools and teachers could implement character education by involving all students through the habituation program for religious activities in schools. (2) Meanwhile, the character values that arise in students include religion, discipline, and responsibility, which are expected to be applied in everyday life.